THE INFLUENCE OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN THE CITY AGUNG DISTRICT OFFICE - Melisa Kurnia Asfitri; Putri Andriyani Simanjuntak; Rahma Dewi; Fadhil Fadhlur Rohman; Fahirah Mayangsari; Muhammad Haudhi Al-Azzah (Journal of Psychology and Social Sciences, 2023)
The purpose of this study was to determine the effect of the workenvironment on employee performance at the Kota Agung sub-districtoffice. The type of research used is comparative causal . Respondentswho resulted from the survey amounted to 37 respondents. The datacollection technique is done by survey online via google form, using 3scales namely Work Environment (X1), Work Attitude (X2), andperformance (Y). The data analysis method for testing the hypothesisuses a simple linear regression method with significant data results,which means that the work environment in the sub-district office ofKota Agung has an effect on employee performance. Based on theresults of research that aims to determine the effect of the workenvironment on employee performance in the district office grand city. It can be seen from the significant value in the data above in the formof 0.000 <0.05 tends to be lower than the significant level which is 0.24.It can be concluded that the work environment variable affects theperformance of employees at the Kota Agung sub-district office or canbe called correlated and thus H0 is rejected or in other words there isan effect. Square Bearing R square is 0.197 which implies that the workenvironment variable has an independent effect on employeeperformance variables by 20.4 percent .